On the Persistence of Economic Fluctuations: Further Evidence From a Classical Nonparametric Approach - Marco Bianchi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
The paper presents a nonparametric approach, based on kernel density estimators, to assess and compare persistence of output fluctuations in Belgium, Canada, France, Germany, Italy, Japan, the United Kingdom and the Unated States. The results obtained are interpreted to be compatible in general with those already derived from the literature, but with some advantages in terms of very easy computation and economic interpretation.
Keywords: 330